A study on the mechanism of the influence of short science video features on people’s environmental willingness in social media—Based on the SOR model - Wang, Xiaofeng; Yue, Xiaoguang (Frontiers in Environmental Science, 2022)
Based on the SOR (Stimulus-Organism-Response) model, the influence of short science videos on people's Environmental Willingness is explored from the perspective of stimulus response, and their intrinsic mechanisms of action are explored. The study finds that the content features of short videos (usefulness, ease of use and entertainment) can positively influence people's environmental willingness through two paths: emotional evocation and perceptual fit. In addition, we should focus on the emotional resonance of people's hearts and bring into play the advantages of sound and picture, so as to enhance and optimize the persuasive effect of short science videos on people.